Effect of beluntas leaf (Pluchea indica) ethanol extract on mortality of instar II larvas (Spodoptera litura F.) on long bean plant (Vigna sinensis L.) - Syamsul Bahri; Ayudya Lestari; Via Monica Devi; Baiq Fitri Rahmayanti; Muhammad Akhyar Rosyidi (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2022)
Low long bean productivity is one of the impacts of S. litura. Farmers often rely on chemical fertilizers to control the population of S. litura so that this control method can leave residues in the growing media. Therefore, an effort to overcome the problem of S. litura is to use natural pesticides from beluntas leaves (P. indica), which produce secondary metabolites. This study aimed to determine the effect of ethanol extract of beluntas (P. indica) leaves on the mortality of second instar larvae of S. litura in long bean plants. This study used a completely randomized design (CRD) consisting of 5 concentrations, namely 50 ppm, 100 ppm, 150 ppm, 200 ppm, and 250 ppm, as well as control using distilled water with two repetitions. Descriptive statistics analyzed the research data. The results showed that the ethanol extract of beluntas leaves affected the mortality of the second instar larvae S. litura by 40.0% at a concentration of 250 ppm. Concentrations of 50 ppm and 100 ppm gave a mortality effect of 10.0%, a concentration of 150 ppm was 15.0%, and a concentration of 200 ppm was 35.0%. Thus it can be concluded that the higher the concentration of the ethanol extract of beluntas leaves, the higher the mortality of the second instar larvae of S. litura.